Emissão e crescimento de folhas e seus efeitos na produção de frutas de duas cultivares de morangueiro - Rosa, Hamilton Telles (2010)
The objectives of this Dissertation were to estimate the base temperature for leaf appearance, to determine the phyllochron, and to characterize leaf area growth and yield components in two strawberry cultivars. A two year field experiment was conducted during 2008 and 2009 at the experimental area of the Crop Science Department, Federal University of Santa Maria, in Santa Maria, RS. The cultivars Arazá (early) and Yvapitá (late) from the Breeding Program of INIA-Uruguay were used. After rooting, seedlings were transplanted to 1,2m x 20m plots with a 10 plants m-² density. Experimental design was a complete randomizes block with four replications. After transplanting, six plants per replication were tagged with colored wines. The main crown number of accumulated leaves of the six tagged plants and the length and width of the central leaflet of two tagged plants were measured on a weekly and on a 15-day ben, respectively. Green leaf area was calculated from leaflet length and width. Base temperature (Tb) was estimated using the Mean Square Error (MSE) approach of the regression between accumulated leaf number (LN) and accumulated thermal time (TT). The phyllochron as the inverse of the slope of the regression of LN against TT. Power law equations were estimated for the allometric relationship between green leaf area and LN on the main crown. Fruit were harvested from the tagged plants when fruits had 75% of the epidermis colored. Fruits were grouped into commercials (fresh weight greater than 10g) and non commercials (fresh weight lower than 10g). Early (from first harvest until last harvest in september) and total (until 15 November) fruit yield was determined in both years. Estimated Tb for leaf appearance in both cultivars was 0°C. The phyllochron varied throughout the developmental cycle, being greater after flowering. There was difference in phyllochron berween the two cultivars and among planting dates, with greater phyllochron in the cultivar Arazá and in late planting dates. There was a good fit of the power function to the allometric relationship between leaf area and leaf number. On the main crown cultivar Arazá had greater early fruit yield. Total yield was more affected by environment than by genetic constitution.